THE AXIOLOGICAL ASPECT OF THE NOTION “TOLERANCE” - V. V. Matyushina (Vestnik MGIMO-Universiteta)
The conception of tolerance in philosophy and linguistics is considered in the article. The article shows the philosophical and sociopolitical nature of the notion “tolerance” together with a special stress on the usage peculiarities of the word “tolerance” in the Russian language. The place of tolerance in the system of values is studied and also its place in the theory of cultural dialogue is defined. There has lately been a discussion among Russian researchers about the phenomenon under consideration - that of tolerance – and its top-importance. The whole terminology ,connected with the problems of tolerance, as well as the very word “tolerance”, are borrowed from English. The analysis of the usage of the Russian equivalents for the term “tolerance” is carried out with the help of the materials devoted to the problems of tolerance. Moreover, an attempt is made to define the status of tolerance as a value of modern society because contemporary philosophy considers tolerance to be one of the fundamental values of the present. As the interaction of cultures is basically a dialogue a modern human being has to overcome stereotypes and become tolerant to realize and appreciate other cultures. Modern society needs some new communication methods based on the respect for different cultures.